Analysis on community involvement in cultural activities: transmission of ethnic - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (MIP, 2014)
This research reviews an analysis of Community Involvement in Cultural Activities specifically from the angle of transmission of Ethnic Language. Convention for the Safeguarding of Intangible Cultural Heritage (ICH) which has been adopted by UNESCO in October, 2003 has aimed to raise awareness at the local, national and international levels of the significance ICH, to ensure ICH is mutually respected by the communities concerned and to provide assistance for education and fund for the maintenance of this heritage. Survey Questionnaires have been recently conducted in one of the World Heritage Site, Melaka; to measure and determine the level of community involvement in cultural activities. The survey adopts five domains of ICH, Oral Tradition, Performing Arts, Knowledge, Social Practices and Traditional Craftsmanship in determining the involvement level of four cultured communities in their cultural enactments. These four communities are selected geographically. They are Morten Village Community, Portuguese Village Community, Heren and Jonker Streets Community and Gajah Berang Village Community. This paper acknowledges the significance, similarities and differences of the four cultured communities especially on transmission of ethnic languages with regards to community characters, specifically demographic and socio-economic factors. Finally the analysis evaluates on the significance ethnic language transmission towards the overall cultural manifestations of the cultural communities.